Efficiency of shuttle operations in UiTM Alor Gajah, Melaka’s students / Muhammad Khairul Aiman Leman - Leman, Muhammad Khairul Aiman (2023)
Public transport was invented in 1828. It was France who, again, tested this public transportation system. This time by saving room for those without blue blood. Its way across the pond to New York City, who had established their own omnibus line by 1828. Soon after, many U.S and European cities followed suit. (Madeline Parks, September 14, 2023). Technology and human life are becoming more and more associated today. This is because technology has made it possible to address problems quickly and easily. Systems or technology can either make people satisfied or dissatisfied. Student’s often use public transportation because of reliable and affordable in the campus. As we know, student’s in the campus can go anywhere just only riding a bus to the destination they want to go. But, the limited resources such as bad routes, bad operation systems and lack of bus may be a barrier for students to use the public transportation. This abstract highlights the detrimental effects of the public transportation among students in the UiTM Campus Alor Gajah, Melaka. This thesis examines the efficiency of shuttle operations at UiTM Campus Alor Gajah, Melaka, with a focus on the experiences and challenges faced by students. Efficient transportation services within a university campus are crucial for students' mobility, convenience, and timely access to various facilities. However, inadequate shuttle operations can lead to delays, overcrowding, and frustration among students. The study analyzes the knowledge and awareness levels of the target audience through survey data analysis and examines the impact of low efficiency of shuttle operations for students. The findings highlight the urgent need for improvements in shuttle operations at UiTM Campus Alor Gajah, Melaka. Recommendations include optimizing bus schedules to align with student demand, increasing bus capacity during peak hours, and establishing effective communication channels to provide timely information to students. By addressing these challenges, the overall efficiency and effectiveness of the shuttle services can be enhanced, ultimately improving the transportation experience for students. This research contributes to the existing literature by providing valuable insights into the specific issues faced by students in relation to shuttle operations at UiTM Campus Alor Gajah, Melaka. The recommendations derived from the findings can inform decision-makers and administrators in implementing targeted improvements to meet the transportation needs of the students effectively